The stimulatory effect of silica nanoparticles on osteogenic differentiation of human mesenchymal stem cells. (2nd December 2016) - Yang, Xing; Li, Yuanyuan; Liu, Xujie; Huang, Qianli; He, Wei; Zhang, Ranran; Feng, Qingling; Benayahu, Dafna
Abstract: Silica-based materials with favourable biocompatibility are generally considered as excellent candidates for applications in biomedical fields. However, previous researches mainly focused on the safety of silica-based materials, their effects on osteogenic differentiation of human mesenchymal stem cells (hMSCs) still need further investigations. In this study, core–shell fluorescent silica nanoparticles (silica NPs) with three different sizes (S1 50 nm, S2 200 nm, S3 400 nm, respectively) were prepared according to the Stöber method. The silica NPs with different sizes did not affect the cell viability (even up to a concentration of 500 µ g ml −1 ), showing size- and dose-independent cytocompatibility of silica NPs on hMSCs. Uptake of silica NPs significantly enhanced the activity of alkaline phosphatase (ALP) and the formation of bone-like nodules of hMSCs after osteogenic induction. At the concentration of 10 µ g ml −1, after treating hMSCs with larger sized silica NPs (S2 and S3), higher ALP activity of hMSCs was measured and larger sized bone-like nodules were formed by hMSCs compared with that treated with smaller sized silica NPs (S1).The enhanced osteogenic potential of hMSCs treated with silica NPs may be attributed to the Si released from silica NPs due to the lysosomal degradation inside hMSCs. These results demonstrate the stimulatory effect of silica NPs on osteogenic differentiation of hMSCs and the application potential of silica NPs in bone tissue engineering.